Determining the dietary preferences of wild Asian elephants (Elephas maximus) in Taman Negara National Park, Malaysia based on sex and age using trnL DNA Metabarcoding Analysis - Nurfatiha Akmal Fawwazah Abdullah-Fauzi; Kayal Vizi Karuppannan; Nor Hafisa Syafina Mohd-Radzi; Millawati Gani; Abd Rahman Mohd-Ridwan; Nursyuhada Othman; Hidayah Haris; Nur Hartini Sariyati; Nor Aifat A. Rahman; Muhammad Abu Bakar Abdul-Latiff; Mohd Firdaus Ariff Abdul-Razak; Badrul Munir Md-Zain (Biodiversity Research Center, Academia Sinica, Taiwan, 2022)
The world’s largest terrestrial mammal, Asian elephants are known to have enormous feeding needs. Several factors such as season, sex, age, and daily activities of elephants influence the amount of food required by an individual. Generally, captive elephants have a limited choice of food on a daily basis compared with that of elephants in the wild. Elephants in captivity are fed according to a prepared feeding schedule, whereas wild elephants are free to choose the type of plants that they consume in their natural habitat. In the past, ecological observations have been widely used to determine the diet of wild elephants. However, the molecular approach was never been carried out. In the present study, the aim was to; 1) identify the plant diet of wild Asian elephants in Taman Negara National Park (TNNP) according to their sex and age using high-throughput DNA metabarcoding 2) determine the dietary formulation of captive elephants based on the generated plant metabarcoding database. DNA was extracted from 24 individual fecal samples collected using noninvasive sampling techniques from TNNP and the National Elephant Conservation Centre (NECC) Kuala Gandah. Seven pooled samples comprising of male adult, female adult, male subadult, female subadult, male juvenile, female juvenile, and captive elephant were amplified and sequenced targeting the trnL region (50–150 base pairs). The CLC Genomic Workbench and PAST 4.02 software were used for data analysis. In total, 24 orders, 41 families, 233 genera, and 306 species of plants were successfully detected in the diet of the Asian elephants. The most abundant plant genera consumed were Sporobolus (21.88%), Musa (21.48%), and Ficus (10.80%). Plant variation was lower in samples from male elephants than in those from female elephants. The plant species identified were correlated with the nutrient benefits required by elephants. Besides, adults and subadults consumed more plant species than were consumed by juvenile elephants. However, there are no significant difference between ages and the two sexes. The findings of this study can be used as guidance by the Department of Wildlife and National Parks for the management of captive elephants, especially in NECC Kuala Gandah.